ИНТЕЛЛЕКТУАЛЛАШТИРИЛГАН ТАЪЛИМ МАЗМУНИНИ ШАКЛЛАНТИРИШ - Тўрақулов, У.Х. (SCIENCE and SOCIETY, 2018)
The article deals with the formation of an intelligent educational content for future teachers to prepare them for their professional career. The article can be used to deal with issues related to intellectual education.
Keywords: future teacher; vocational education; intellectual; educational content; knowledge; skill; habits; intellectual resources; intellectual potential; intellectual activity; content; formation; innovation; expertise; induction; integration; interactive